Investigation for a multi-silique trait in Brassica napus by alternative splicing analysis - Chai, Liang; Zhang, Jinfang; Li, Haojie; Zheng, Benchuan; Jiang, Jun; Cui, Cheng; Jiang, Liangcai (PeerJ, 2020)
Background Flower and fruit development are vital stages of the angiosperm lifecycle. We previously investigated the multi-silique trait in the rapeseed (Brassica napus) line zws-ms on a genomic and transcriptomic level, leading to the identification of two genomic regions and several candidate genes associated with this trait. However, some events on the transcriptome level, like alternative splicing, were poorly understood. Methods Plants from zws-ms and its near-isogenic line (NIL) zws-217 were both grown in Xindu with normal conditions and a colder area Ma’erkang. Buds from the two lines were sampled and RNA was isolated to perform the transcriptomic sequencing. The numbers and types of alternative splicing (AS) events from the two lines were counted and classified. Genes with AS events and expressed differentially between the two lines, as well as genes with AS events which occurred in only one line were emphasized. Their annotations were further studied. Results From the plants in Xindu District, an average of 205,496 AS events, which could be sorted into five AS types, were identified. zws-ms and zws-217 shared highly similar ratios of each AS type: The alternative 5′ and 3′ splice site types were the most common, while the exon skipping type was observed least often. Eleven differentially expressed AS genes were identified, of which four were upregulated and seven were downregulated in zws-ms. Their annotations implied that five of these genes were directly associated with the multi-silique trait. While samples from colder area Ma’erkang generated generally reduced number of each type of AS events except for Intron Retention; but the number of differentially expressed AS genes increased significantly. Further analysis found that among the 11 differentially expressed AS genes from Xindu, three of them maintained the same expression models, while the other eight genes did not show significant difference between the two lines in expression level. Additionally, the 205 line-specific expressed AS genes were analyzed, of which 187 could be annotated, and two were considered to be important. Discussion This study provides new insights into the molecular mechanism of the agronomically important multi-silique trait in rapeseed on the transcriptome level and screens out some environment-responding candidate genes.
Keywords: Alternative splicing; Brassica napus; Differentially expressed gene; Multi-silique; Transcriptome sequencing